Implementing Dynamically Evolvable Communication with Embedded Systems through WEB Services - Sasi Bhanu Jammalamadaka; Vinaya Babu A; Trimurthy A (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Embedded systems that monitor and control safety and mission critical system are communicated with by a HOST located at a remote location through Internet. Such kind of embedded systems are developed to be dynamically evolvable with respect to syntax, semantics, online testing and communication subsystems. All these systems are to be dynamically evolvable and the components needed for evolution are also to be added into the embedded system. Architectural  models describe  various components using which dynamically evolvable sub-systems are realised through implementation by using specific and related technologies. Implementation system describe the platform, code units and the interlacing of various processes/tasks to the elementary level of details. WEB services place an excellent platform for implementing dynamically evolvable  systems due to the use of open standards. This paper presents an implementation system that is related to dynamically evolvable communication and other sub-systems using web services technologies.